Current Heart Failure Reports - Colucci, Wilson S.; Angermann, Christiane E.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
This journal intends to provide clear, insightful, balanced contributions by international experts that review the most important, recently published clinical findings related to the diagnosis, treatment, management, and prevention of heart failure. We accomplish this aim by appointing international authorities to serve as Section Editors in key subject areas, such as investigative, pharmacologic, and nonpharmacologic therapies, pathophysiology, and prevention. Section Editors, in turn, select topics for which leading experts contribute comprehensive review articles that emphasize new developments and recently published papers of major importance, highlighted by annotated reference lists. An international Editorial Board reviews the annual table of contents, suggests articles of special interest to their country/region, and ensures that topics are current and include emerging research. Commentaries from well-known figures in the field are also provided.
Keywords: Radiology; Internal medicine; Cardiology; Cardiac surgery; Vascular surgery; Cardiology; Cardiac Surgery; Vascular Surgery; Internal Medicine; Imaging / Radiology